Time-Varying Impact of Crude Oil Prices on Indian Auto Stock Returns: A Rolling Window and Structural Break Analysis (International Journal of Environmental Sciences, 2025)
This study examines the dynamic impact of crude oil prices on the returns of selected Indian automotive firms with the help of a large econometric model. Utilizing monthly data from the period January 2010 to December 2024, the work employs Augmented Dickey-Fuller tests, dummy variable regressions, rolling window regressions, and Bai-Perron structural break tests to examine whether investor responses to crude oil prices and key macroeconomic variables—exchange rate, interest rate, and inflation—have evolved over time. These findings point towards an abrupt decline in oil price sensitivity post-2016, particularly in the case of Tata Motors and the Nifty Auto Index, concurring with key policy actions like the FAME II scheme and fuel price deregulation in India. Maruti Suzuki is found to be exchange rate volatility sensitive, while CPI is found to have minimal impact across the sector. Structural breakpoints overlap with significant policy shifts and macro shocks like the COVID-19 pandemic. Finally, the study emphasizes that investor sentiment has adapted in response to structural reforms, demonstrating a gradual decoupling of auto stock performance from crude oil price volatility. The results are helpful to investors, policymakers, and market participants in understanding India's evolving auto sector and energy landscape.